Urban immunity against the pandemic within the framework of public administration, city and citizens - Negiz, Nilüfer (Central European Public Administration Review, 2021)
The circumstances arising in connection with the Covid-19 pandemic indicate that outbreaks are inevitable and that new pandemics are quite likely. Cities, just like people, need to protect themselves from pandemics. Therefore, the existing urban and spatial practices should be reconsidered. The aim of the study is to explore, by observation and literature review, the cities' readiness for possible pandemics or emergencies within the framework of the concept of urban immunity. Based on the elements necessary for the provision of immunity in humans, the requirements for urban immunity, the health of the infrastructure and super - structure of the soil, the resources and sustainability of a city, its resilience and growth control are discussed within the framework of urban management. In addition, the study identifies three indispensable actors for urban immunity: i) central governments, ii) local governments, and iii) citizens. Immunized cities can be defined as cities with healthy infrastructure and superstructure factors of urban soil aiming at economic and ecological sustainability that have achieved a planned and controlled growth momentum, governed by public policies created with the understanding of local welfare and democracy in cooperation with local governments, citizens, and the central government. The study is purely theoretical and focuses on universal urban immunity rather than on any country example, which constitutes the strength of the study.
Keywords: central government; COVID-19; državna uprava; immunized city; javna uprava; local government; lokalna samouprava; pandemic; pandemija; urban immunity; urbana imunost